PENGARUH MANAJEMEN PROSES TERHADAP KUALITAS PELAYANAN DI HOTEL BUNDA BUKITTINGGI - Yulhaslinda Yulhaslinda; Rika Andriani (Ensiklopedia Sosial Review, 2022)
This research aims to analyze the quality of service at Bunda Bukittinggi hotel in terms of management. The number of population in this study is all employees at Bunda Bukittinggi Hotel, both contract employees and permanent employees, which amounts to 31 employees. Then the sample in this study is the entire population using the census method which means the entire population becomes a sample. Then conducted a research instrument test with a validity test and reliability test. Before the double linear regression test, a classic assumption test was conducted with a test of normality, linearity, multicollinearity and so on. From the results of the double linear regression test, the results were obtained that management variables had a positive and significant influence on the Quality of Service at Bunda Bukittinggi Hotel.